Pemanfaatan Lahan Pekarangan Rumah dengan Membuat Budidaya Vertikultur Farming di Masa Pasca Pandemi oleh Tim Kukerta UNRI 2022 - M. Ryandi Putra Budi Madali; Indah Fadila; El Firdausia Yahfis; Nur Elviana Dewi; Vena Dunya; Atika Nadhifah; Bella Indriani; Rafi Palabuti; Gibrani Azhardi; Fabian Pradipta (LP2M Universitas Muhammadiyah Enrekang, 2022)
Verticulture is an agricultural cultivation system that is carried out in a vertical and multilevel way on an indoor and outdoor scale. By and large, verticulture is carried out with a specific container for its cultivation depending on the conditions of the premises and desire. Students of Kukerta Unri, Padang Bulan Village, chose the method of planting verticulture farming, because this verticulture farming is suitable for use in the Padang Bulan Village area which has minimal vacant land. The verticulture farming method is generally carried out using a certain container as a planting medium, depending on the conditions of the place and desire. Although it may seem difficult at first glance, the verticulture system of planting is quite easy to implement. Verticulture media made in the form of large and small PVC pipes in white. Large pipe measuring 4 inch small pipe measuring 1 inch. The seeds used are pakcoy vegetable seeds, celery and lettuce. The seedling is then planted in each hole in a large pipe. The use of vitamin AB MIX in watering seedlings, then harvesting activities are carried out 26 days after the vegetable is planted. Furthermore, the Lurah and the staff of Padang Bulan Village harvested pakcoy, celery and lettuce that were worthy of harvest at the lurah office.